Mo-doped polyanion positive electrode material, preparation method and application
The Mo-doped polyanion cathode material addresses stability and toxicity issues in sodium ion batteries by reducing Na+ migration barriers and enabling efficient charge compensation, resulting in high energy density and long cycle life for large-scale energy storage applications.
Patent Information
- Application Number
- CN202110505342.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-05-10
AI Technical Summary
Current sodium ion battery positive materials face challenges such as poor chemical and electrochemical stability, limited thermal stability, and toxicity issues, which hinder their large-scale application, particularly due to the limitations of traditional layered oxide materials and Prussian blue analogs.
Development of a Mo-doped polyanion cathode material with the chemical formula NabMnxTiyMoaMz(PO4)3, where M includes elements like Fe3+, Zn2+, Mg2+, and others, which reduces the Na+ migration barrier and enables three pathways for Na+ migration, stabilizing the structure and enhancing electrochemical performance.
The Mo-doped polyanion cathode material achieves high energy density, excellent cycle life, and practical value for large-scale energy storage in applications like solar and wind energy, smart grids, and communication base stations, with improved Mn element valence changes for efficient charge compensation.
Smart Images

Figure CN115332529B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a Mo-doped polyanion positive electrode material and a preparation method thereof and a sodium ion battery. Background Art
[0002] In recent years, the energy industry and energy storage technology have received much attention. Due to its high energy density and high power density, lithium-ion battery (LIB) technology stands out from many energy storage devices, and has made great progress in recent decades, greatly revolutionizing human lifestyles. However, lithium resources are unevenly distributed on the earth and their content is limited, which greatly hinders the application of lithium-ion batteries in large-scale energy storage devices. In order to alleviate the problem of lithium resource shortage, sodium-ion batteries are considered to be one of the most promising alternatives. Sodium resources are abundant on the earth, low cost and environmentally friendly, which makes sodium-ion batteries promising for large-scale energy storage systems that do not require high energy density. The development of low-cost, environmentally friendly and excellent performance sodium-ion battery cathode materials is of great significance for their promotion and application. Poor chemical and electrochemical stability restricts the application prospects of traditional layered oxide cathode materials. Prussian blue analogues are due to their low cost, easy synthesis at low temperature, and Na + Prussian blue has been widely studied due to its low activation energy for insertion / extraction. However, their poor thermal stability, low volume density and cyanide toxicity are inherent limitations for the practical application of Prussian blue as a cathode for sodium-ion batteries. Another important category of sodium-ion battery cathodes is polyanionic compounds with an open framework structure. Strong X–O (X=P, S, Si or B) covalent bonds provide high structural stability and relatively small volume changes during the insertion and extraction of sodium ions. In the polyanion framework series, the Na + Compounds related to fast ion conductors (NAS I CON) have attracted much attention because of their high Na + Mobility and capacity. However, selecting the right elements and making the best use of their capacity is still a challenge. Summary of the invention
[0003] The purpose of the present invention is to design a Mo-doped polyanion positive electrode material to successfully achieve the synthesis of a sodium ion battery positive electrode material with low cost, high energy density and large-scale manufacturing by targeting the defects of existing sodium ion battery positive electrode materials. The material not only has high mass specific capacity and specific energy, but also has excellent cycle life and great practical value, and can be used for large-scale energy storage equipment of solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
[0004] In a first aspect, an embodiment of the present invention provides a Mo-doped polyanion cathode material, wherein the Mo-doped polyanion cathode material has a chemical formula of: Nab Mn x T i y Mo a M z (PO4)3; wherein a=0.01-0.2, b=2.5-4.0, x=0.8-1.5, y=0.5-1.2, z=0-0.5; M is an element co-doped with Mo, including: Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , A l 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc 3+ One or more of; the valence state of the element Mo is +6, where Mo 6+ The doping of Na + The migration barrier of the Mo-doped polyanion cathode material is Na + The cathode material migrates through three pathways, including: from the Na1 position to the Na2 position in the NAS I CON structure, through the gap between the PO4 tetrahedron and the MO6 octahedron, and across the channel between adjacent MO6 octahedrons; thereby causing the valence state of the Mn element used for charge compensation in the process of sodium insertion and extraction of the cathode material to be in the Mn 2+ -Mn 3+ -Mn 4+ Transition between.
[0005] Preferably, the Mo-doped polyanion positive electrode material is used as a positive electrode active material for a sodium ion secondary battery.
[0006] In a second aspect, an embodiment of the present invention provides a method for preparing the Mo-doped polyanion positive electrode material according to the first aspect, which is a solid phase method, comprising:
[0007] The required stoichiometric amounts of 100 wt% to 120 wt% of Na source, phosphorus source, Mn source, Ti source, Mo source, M source and carbon source are mixed in proportion to form a precursor; wherein M is an element co-doped with Mo, specifically including Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , A l 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc3+ One or more of;
[0008] Ball-milling the precursor to obtain precursor powder;
[0009] Placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 550° C. to 850° C. for 2 to 24 hours;
[0010] The heat-treated product is ground to obtain the Mo-doped polyanion positive electrode material.
[0011] Preferably, the Na source includes one or more of sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium acetate (CH3COONa), sodium oxalate (Na2C2O4), sodium nitrate (NaNO2), sodium sulfate (Na2SO4), sodium bisulfate (NaHSO4), and sodium citrate (C6H5Na3O7);
[0012] The phosphorus source includes one or more of ammonium dihydrogen phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), phosphoric acid (H3PO4), disodium hydrogen phosphate (Na2HPO4), and sodium dihydrogen phosphate (NaH2PO4);
[0013] The Ti source includes: titanium isopropoxide (C 12 H 28 O4Ti), tetrabutyl titanate (C 16 H 36 One or more of titanium dioxide (TiO2), titanium oxysulfate (TiOSO4), and titanium sulfate (Ti(SO4)2);
[0014] The Mn source includes one or more of manganese acetate (Mn(CH3COO)2), manganese monoxide (MnO), manganese dioxide (MnO2), manganese tetraoxide (Mn3O4), manganese carbonate (MnCO3), manganese sulfate (MnSO4), manganese oxalate (MnC2O4), and manganese nitrate (Mn(NO3)2);
[0015] The Mo source includes: ammonium molybdate ((NH4)6Mo7O 24 ), phosphomolybdic acid (H3PMo 12 O 40 ), ammonium phosphomolybdate ((NH4)3PMo 12 O 40 ), molybdenum trioxide (MoO3), molybdenum dioxide (MoO2), molybdenum acetate (C8H 12Mo2O8), molybdenum dioxide nitrate (MoO2(NO3)2), molybdenum dioxide acetylacetonate (C 10 H 14 MoO6) one or more;
[0016] The carbon sources include glucose (C6H 12 O6), starch, citric acid (C6H8O7), ascorbic acid (C6H8O6), polyvinyl alcohol, polyethylene oxide, polydopamine, polyacrylonitrile, polyvinyl pyrrolidone, carbon nanotubes, carbon fibers, and graphene;
[0017] The M source includes: an oxide corresponding to the M element (M x O y ), acetate (M(CH3COO) z ), nitrate (M(NO3) z ) one or more.
[0018] In a third aspect, an embodiment of the present invention provides a method for preparing the Mo-doped polyanion positive electrode material according to the first aspect, which is a sol-gel method, comprising:
[0019] The required stoichiometric amounts of 100wt% to 120wt% of Na source, phosphorus source, Ti source, Mn source, Mo source, M source and carbon source are mixed in proportion, dispersed with a solvent and continuously heated and stirred to form a gel, and evaporated to obtain a precursor powder; wherein M is an element co-doped with Mo, specifically Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , A l 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc 3+ One or more of;
[0020] Placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 550° C. to 850° C. for 2 to 24 hours;
[0021] The heat-treated product is ground to obtain the Mo-doped polyanion positive electrode material.
[0022] Preferably, the Na source includes one or more of sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium acetate (CH3COONa), sodium oxalate (Na2C2O4), sodium nitrate (NaNO2), sodium sulfate (Na2SO4), sodium bisulfate (NaHSO4), and sodium citrate (C6H5Na3O7);
[0023] The phosphorus source includes one or more of: ammonium dihydrogen phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), phosphoric acid (H3PO4), disodium hydrogen phosphate (Na2HPO4), sodium dihydrogen phosphate (NaH2PO4);
[0024] The Ti source includes: titanium isopropoxide (C 12 H 28 O4Ti), tetrabutyl titanate (C 16 H 36 One or more of titanium dioxide (TiO2), titanium oxysulfate (TiOSO4), and titanium sulfate (Ti(SO4)2);
[0025] The Mn source includes one or more of manganese acetate (Mn(CH3COO)2), manganese monoxide (MnO), manganese dioxide (MnO2), manganese tetraoxide (Mn3O4), manganese carbonate (MnCO3), manganese sulfate (MnSO4), manganese oxalate (MnC2O4), and manganese nitrate (Mn(NO3)2);
[0026] The Mo source includes: ammonium molybdate ((NH4)6Mo7O 24 ), phosphomolybdic acid (H3PMo 12 O 40 ), ammonium phosphomolybdate ((NH4)3PMo 12 O 40 ), molybdenum trioxide (MoO3), molybdenum dioxide (MoO2), molybdenum acetate (C8H 12 Mo2O8), molybdenum dioxide nitrate (MoO2(NO3)2), molybdenum dioxide acetylacetonate (C 10 H 14 MoO6) one or more;
[0027] The carbon sources include glucose (C6H 12 O6), starch, citric acid (C6H8O7), ascorbic acid (C6H8O6), polyvinyl alcohol, polyethylene oxide, polydopamine, polyacrylonitrile, polyvinyl pyrrolidone, carbon nanotubes, carbon fibers, and graphene;
[0028] The M source includes: an oxide corresponding to the M element (M x O y ), acetate (M(CH3COO) z ), nitrate (M(NO3) z )
[0029] The solvent includes one or more of water, methanol, ethanol and ethylene glycol.
[0030] In a fourth aspect, an embodiment of the present invention provides a method for preparing the Mo-doped polyanion positive electrode material according to the first aspect, which is a spray drying method, comprising:
[0031] The required stoichiometric amounts of 100wt% to 120wt% of Na source, phosphorus source, Ti source, Mn source, Mo source, M source and carbon source are mixed in proportion, dispersed with a solvent and continuously heated and stirred to form a slurry; wherein M is an element co-doped with Mo, specifically Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , A l 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc 3+ , Nb 5+ , Sc 3+ One or more of;
[0032] Spray drying the slurry to obtain a precursor powder;
[0033] Placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 550° C. to 850° C. for 2 to 24 hours;
[0034] The heat-treated product is ground to obtain the Mo-doped polyanion positive electrode material.
[0035] Preferably, the Na source includes one or more of sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium acetate (CH3COONa), sodium oxalate (Na2C2O4), sodium nitrate (NaNO2), sodium sulfate (Na2SO4), sodium bisulfate (NaHSO4), and sodium citrate (C6H5Na3O7);
[0036] The phosphorus source includes one or more of: ammonium dihydrogen phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), phosphoric acid (H3PO4), disodium hydrogen phosphate (Na2HPO4), sodium dihydrogen phosphate (NaH2PO4);
[0037] The Ti source includes: titanium isopropoxide (C 12 H 28 O4Ti), tetrabutyl titanate (C 16 H 36 One or more of titanium dioxide (TiO2), titanium oxysulfate (TiOSO4), and titanium sulfate (Ti(SO4)2);
[0038] The Mn source includes one or more of manganese acetate (Mn(CH3COO)2), manganese monoxide (MnO), manganese dioxide (MnO2), manganese tetraoxide (Mn3O4), manganese carbonate (MnCO3), manganese sulfate (MnSO4), manganese oxalate (MnC2O4), and manganese nitrate (Mn(NO3)2);
[0039] The Mo source includes: ammonium molybdate ((NH4)6Mo7O 24 ), phosphomolybdic acid (H3PMo 12 O 40 ), ammonium phosphomolybdate ((NH4)3PMo 12 O 40 ), molybdenum trioxide (MoO3), molybdenum dioxide (MoO2), molybdenum acetate (C8H 12 Mo2O8), molybdenum dioxide nitrate (MoO2(NO3)2), molybdenum dioxide acetylacetonate (C 10 H 14 MoO6) one or more;
[0040] The carbon sources include glucose (C6H 12 O6), starch, citric acid (C6H8O7), ascorbic acid (C6H8O6), polyvinyl alcohol, polyethylene oxide, polydopamine, polyacrylonitrile, polyvinyl pyrrolidone, carbon nanotubes, carbon fibers, and graphene;
[0041] The M source includes: an oxide corresponding to the M element (M x O y ), acetate (M(CH3COO) z ), nitrate (M(NO3) z )
[0042] The solvent includes one or more of water, methanol, ethanol and ethylene glycol.
[0043] In a fifth aspect, an embodiment of the present invention provides a positive electrode plate for a sodium ion secondary battery, comprising: a current collector, a conductive additive coated on the current collector, a binder, and the Mo-doped polyanion positive electrode material as described in the first aspect above.
[0044] In a sixth aspect, an embodiment of the present invention provides a sodium ion secondary battery comprising the positive electrode plate described in the fifth aspect above.
[0045] The present invention provides a Mo-doped polyanion sodium ion battery positive electrode material containing Ti and Mn. 3- The framework makes the material maintain structural stability during the process of sodium insertion and extraction; secondly, in the Mo-doped polyanion positive electrode material, Mo 6+ The doping of Na + The migration barrier of Na + There are three migration pathways, including: migration from the Na1 position to the Na2 position in the NAS I CON structure, through the gap between the PO4 tetrahedron and the MO6 octahedron, and migration across the channel between adjacent MO6 octahedrons; thereby promoting the valence state of the Mn element used for charge compensation in the process of sodium insertion and extraction in the positive electrode material to be in the Mn 2+ -Mn 3+ -Mn 4+ The material can be transformed between the two electrodes to realize two electron transfers and a higher voltage platform, so that the material has a high energy density. The present invention further improves the capacity and cycle performance of the material by adding Mo. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0047] Figure 1 A schematic diagram of the crystal structure of the Mo-doped polyanion positive electrode material provided by the present invention;
[0048] Figure 2 The Na in the Mo-doped polyanion positive electrode material provided by the present invention + Schematic diagram of the three migration pathways;
[0049] Figure 3 The X-ray diffraction (XRD) data of Example 4 of the present invention and the Rietveld method refinement result thereof;
[0050] Figure 4 The XRD patterns of Examples 1, 4 to 7 and Comparative Examples 1 to 3 of the present invention are shown below;
[0051] Figure 5This is a comparison chart of the first week charge and discharge curves of Comparative Examples 1-3 at a rate of 0.1C (1C = 117 mAh / g);
[0052] Figure 6 It is a comparison diagram of the first week charge and discharge curves of Examples 1, 4, 5, 9, 10 and Comparative Example 1 at a rate of 0.1C;
[0053] Figure 7 This is a comparison diagram of the first-week charge and discharge curves of Examples 19, 20, and 21 of the present invention at a rate of 0.1C;
[0054] Figure 8 The rate test curves of Example 4 of the present invention and Comparative Example 1 at rates of 0.05C, 0.1C, 0.2C, 0.5C, 1C, and 2C respectively;
[0055] Fig. 9 It is a comparison diagram of the cycle test curves of Example 4 of the present invention and Comparative Example 1 at a rate of 0.5C. DETAILED DESCRIPTION
[0056] The present invention is further described below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0057] The Mo-doped polyanion positive electrode material of the present invention has the general chemical formula: Na b Mn x T i y Mo a M z (PO4)3; wherein a=0.01-0.2, b=2.5-4.0, x=0.8-1.5, y=0.5-1.2, z=0-0.5; M is an element co-doped with Mo, including: Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , A l 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc 3+ One or more of the following. The space group of the Mo-doped polyanion cathode material of the present invention is Crystal structure diagram Figure 1 shown.
[0058] The valence state of the element Mo is +6. In the Mo-doped polyanion positive electrode material of the present invention, Mo6+ The doping of Na + Migration barriers, such as Figure 2 As shown, in the Mo-doped polyanion cathode material, Na + It migrates through three pathways, including: from the Na1 position to the Na2 position in the NAS I CON structure, through the gap between the PO4 tetrahedron and the MO6 octahedron, and across the channel between adjacent MO6 octahedrons, thereby promoting the valence state of the Mn element used for charge compensation in the process of sodium insertion and extraction in the positive electrode material. 2+ -Mn 3+ -Mn 4+ Specifically, in the present invention, the polyanion material is used as the positive active material of the sodium ion secondary battery. During charging, the manganese ions in the lattice lose electrons, and the average valence increases from +2 to +4; during discharge, the manganese ions gain electrons, and the average valence changes from +4 to +2. The Mo-doped polyanion positive electrode material of the present invention is used as the positive active material of the sodium ion secondary battery.
[0059] For traditional manganese ion valence-changing positive electrode active materials, how to achieve Mn 2+ / Mn 4+ The reversible valence of Na3TiMn(PO4)3 has always been a difficulty in the positive electrode materials of secondary batteries. In the study, we found that increasing its conductivity by adjusting the carbon content did not make the Mn 2+ The valence is fully changed to achieve the theoretical specific capacity. In addition, since carbon is an inactive material, the introduction of excessive carbon will also affect the capacity of Na3TiMn(PO4)3@C.
[0060] The invention is based on our research findings that the introduction of a small amount of Mo element can significantly increase the capacity of Na3TiMn(PO4)3. It is particularly noteworthy that since the Mo element in this system is mainly Mo 6+ It exists in the form of, which is a high-valent element. The introduction of Mo element plays a role in the following three aspects:
[0061] 1.Mo 6+ It is a hexavalent impurity atom. The excess valence electrons can easily form free electrons (N-type doping) because they are not bound by covalent bonds. Due to the movement of the Fermi level, the electronic conductivity of the material is improved to a certain extent.
[0062] 2.Mo 6+ The introduction of affects the local Na + Distribution: Mo 6+ The doping of Na + The migration barrier of Na +Migrate through three paths, such as Figure 2 As shown in the figure, it includes: path 1, migration from Na1 position to Na2 position in NAS I CON structure, path 2, passing through the gap between PO4 tetrahedron and MO6 octahedron, and path 3, migration across the channel between adjacent MO6 octahedrons; the circle and arrow in the figure indicate Na + The migration path is shown in Figure 2.
[0063] 3.Mo 6+ The ionic radius With Ti 4+ The ionic radius Therefore, Mo doping will not cause serious lattice distortion.
[0064] Due to the above three advantages, the introduction of Mo element has significant advantages for the system. It can be seen from the text of the present invention that the capacity, rate performance and cycle performance of the doped material are significantly improved.
[0065] The Mo-doped polyanion positive electrode material of the embodiment of the present invention can be prepared by a solid phase method, a sol-gel method or a spray drying method.
[0066] Among them, solid phase methods include:
[0067] Step 11, mixing the required stoichiometric amounts of 100wt% to 120wt% of Na source, phosphorus source, Mn source, Ti source, Mo source, M source and carbon source in proportion to form a precursor; wherein M is an element co-doped with Mo, specifically including Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , A l 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc 3+ One or more of;
[0068] Step 12, ball milling the precursor to obtain precursor powder;
[0069] Step 13, placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 550° C. to 850° C. for 2 to 24 hours;
[0070] Step 14, grinding the product after heat treatment to obtain Mo-doped polyanion positive electrode material.
[0071] Among them, the sol-gel method includes:
[0072] Step 21, mixing the required stoichiometric amounts of 100wt% to 120wt% of Na source, phosphorus source, Ti source, Mn source, Mo source, M source and carbon source in proportion, dispersing with a solvent and continuously heating and stirring to form a gel, and evaporating to obtain a precursor powder; wherein M is an element co-doped with Mo, specifically Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , A l 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc 3+ One or more of;
[0073] Step 22, placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 550° C. to 850° C. for 2 to 24 hours;
[0074] Step 23, grinding the product after the heat treatment to obtain a Mo-doped polyanion positive electrode material.
[0075] Spray drying methods include:
[0076] Step 31, mixing the required stoichiometric amounts of 100wt% to 120wt% of Na source, phosphorus source, Ti source, Mn source, Mo source, M source and carbon source in proportion, dispersing with a solvent and continuously heating and stirring to form a slurry; wherein M is an element co-doped with Mo, specifically Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , A l 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc 3+ , Nb 5+ , Sc 3+ One or more of;
[0077] Step 32, spray drying the slurry to obtain a precursor powder;
[0078] Step 33, placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 550° C. to 850° C. for 2 to 24 hours;
[0079] Step 34, grinding the product after the heat treatment to obtain a Mo-doped polyanion positive electrode material.
[0080] The above three methods are all commonly used methods for preparing positive electrode materials for sodium ion batteries. Those skilled in the art can know how to implement the above preparation methods based on the above records, and will not be described in detail here. The carbon source introduced in the above methods exists in the positive electrode material in the form of amorphous carbon coating after pyrolysis.
[0081] The various sources involved in the above three methods are as follows:
[0082] The Na source includes one or more of sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium acetate (CH3COONa), sodium oxalate (Na2C2O4), sodium nitrate (NaNO2), sodium sulfate (Na2SO4), sodium bisulfate (NaHSO4), and sodium citrate (C6H5Na3O7);
[0083] The phosphorus source includes one or more of ammonium dihydrogen phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), phosphoric acid (H3PO4), disodium hydrogen phosphate (Na2HPO4), sodium dihydrogen phosphate (NaH2PO4);
[0084] Ti sources include: titanium isopropoxide (C 12 H 28 O4Ti), tetrabutyl titanate (C 16 H 36 One or more of titanium dioxide (TiO2), titanium oxysulfate (T iOSO4), and titanium sulfate (Ti(SO4)2);
[0085] The Mn source includes one or more of manganese acetate (Mn(CH3COO)2), manganese monoxide (MnO), manganese dioxide (MnO2), manganese tetraoxide (Mn3O4), manganese carbonate (MnCO3), manganese sulfate (MnSO4), manganese oxalate (MnC2O4), and manganese nitrate (Mn(NO3)2);
[0086] Mo sources include: ammonium molybdate ((NH4)6Mo7O 24 ), phosphomolybdic acid (H3PMo 12 O 40 ), ammonium phosphomolybdate ((NH4)3PMo 12 O 40 ), molybdenum trioxide (MoO3), molybdenum dioxide (MoO2), molybdenum acetate (C8H 12 Mo2O8), molybdenum dioxide nitrate (MoO2(NO3)2), molybdenum dioxide acetylacetonate (C 10 H 14 MoO6) one or more;
[0087] Carbon sources include: glucose (C6H 12 O6), starch, citric acid (C6H8O7), ascorbic acid (C6H8O6), polyvinyl alcohol, polyethylene oxide, polydopamine, polyacrylonitrile, polyvinyl pyrrolidone, carbon nanotubes, carbon fibers, and graphene;
[0088] The M source includes: the oxide corresponding to the M element (M x O y ), acetate (M(CH3COO) z ), nitrate (M(NO3) z ) one or more.
[0089] The solvents involved in the above sol-gel method and spray drying method include one or more of water, methanol, ethanol, and ethylene glycol.
[0090] Those skilled in the art can select the required materials from the above materials to implement the above preparation method according to actual needs.
[0091] The Mo-doped polyanion sodium ion battery positive electrode material containing Ti and Mn provided by the present invention has a stable PO4 3- The framework makes the material maintain structural stability during the process of sodium insertion and extraction; secondly, in the Mo-doped polyanion positive electrode material, Mo 6+ The doping of Na + The migration barrier of Na + The migration of Mn has the above three paths, and the valence state of Mn element used for charge compensation in the process of sodium insertion and extraction in the positive electrode material is Mn 2+ -Mn 3+ -Mn 4+ The material has a high energy density and can achieve two electron transfers, thus realizing a higher voltage platform. The present invention further improves the capacity and cycle performance of the material by adding Mo.
[0092] The Mo-doped polyanion positive electrode material of the present invention can be used as a positive electrode active material and coated on a current collector together with a conductive additive and a binder to form a positive electrode sheet of a sodium ion secondary battery. The positive electrode sheet is used to prepare a sodium ion secondary battery, which can be used for large-scale energy storage equipment for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
[0093] In order to better understand the technical solution provided by the present invention, the following uses a number of specific examples to illustrate the specific process of preparing Mo-doped polyanion positive electrode materials using several methods provided in the above embodiments of the present invention, as well as the method and battery characteristics of applying them to sodium ion secondary batteries.
[0094] Example 1
[0095] This embodiment provides a Mo-doped polyanion material containing Ti and Mn prepared by a sol-gel method, and the preparation process includes:
[0096] Step 101, 3.15 mol (5% excess) Na2CO3, 0.95 mol Ti(SO4)2, 0.95 mol Mn(CH3COO)2 and 1 mol polyvinyl alcohol are mixed and dissolved in ethanol to obtain solution A, and 0.1 mol (NH4)6Mo7O 24 , 3 mol NH4H2PO4 were mixed and dissolved in water to obtain solution B;
[0097] Step 102, slowly adding solution B to solution A under stirring at 80°C until a gel is formed;
[0098] Step 103, drying the gel precursor at 120° C. and grinding to obtain precursor powder;
[0099] Step 104, placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 650° C. for 4 hours;
[0100] Step 105, grinding the heat-treated product to obtain the Mo-doped polyanion material Na containing Ti and Mn. 2.7 Mn 0.95 T i 0.95 Mo 0.1 (PO4)3.
[0101] Example 2
[0102] This embodiment provides a Mo-doped polyanion material containing Ti and Mn prepared by a solid phase method, and the preparation process includes:
[0103] Step 201, 3.15 mol (5% excess) Na2CO3, 0.95 mol Ti(SO4)2, 0.95 mol Mn(CH3COO)2, 0.1 mol (NH4)6Mo7O 24 , 3 mol of NH4H2PO4 and 1 mol of polyvinyl alcohol;
[0104] Step 202, mixing the mixture obtained in the previous step with ethanol, and using a wet grinding method, ball milling at 400 rpm for 24 hours to obtain a uniformly dispersed precursor;
[0105] Step 203, drying the ball-milled precursor at 60° C. to obtain precursor powder;
[0106] Step 204, placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 650°C for 4 hours;
[0107] Step 205, grinding the heat-treated product to obtain Mo-doped polyanion material Na containing Ti and Mn 2.7 Mn 0.95 T i 0.95 Mo 0.1 (PO4)3.
[0108] Example 3
[0109] This embodiment provides a Mo-doped polyanion material containing Ti and Mn prepared by a spray drying method, and the preparation process includes:
[0110] Step 301: 3.15 mol (5% excess) Na2CO3, 0.95 mol Ti(SO4)2, 0.95 mol Mn(CH3COO)2 and 1 mol polyvinyl alcohol are mixed and dissolved in ethanol to obtain solution A. 0.1 mol (NH4)6Mo7O 24 , 3 mol NH4H2PO4 were mixed and dissolved in water to obtain solution C;
[0111] Step 302, spray drying the solution C at 150°C to obtain a precursor powder;
[0112] Step 303, placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 650° C. for 4 hours;
[0113] Step 304, grinding the heat-treated product to obtain the Mo-doped polyanion material Na containing Ti and Mn. 2.7 Mn 0.95 T i 0.95 Mo 0.1 (PO4)3.
[0114] According to the methods provided in the above examples 1-3, different M elements were added and the addition ratio of each element was changed to obtain examples 4-22. In addition, according to the method of the above example 1, no Mo element was added, and the addition ratio of other elements was changed accordingly to obtain comparative examples 1, 2, and 3. See below for details.
[0115] Table 1.
[0116]
[0117]
[0118] Table 1
[0119] The performance of the extracted parts in the above embodiments and comparative examples was tested:
[0120] A. X-ray diffraction (XRD) test
[0121] Select Examples 1, 4 to 7 of the present invention and Comparative Examples 1 to 3, and use Bruker D8 ADVANCE X-ray analyzer and its system to perform XRD test. Figure 3 , Figure 4 .in, Figure 3 The X-ray diffraction (XRD) data of Example 4 of the present invention and the Rietveld method refinement result thereof; Figure 4 The XRD spectra of Examples 1, 4 to 7 of the present invention and Comparative Examples 1 to 3 are shown. The results show that the synthesis methods of Examples 1, 4 to 7 of the present invention can all obtain high-purity Mo-doped polyanion positive electrode materials.
[0122] B. Electrochemical Test
[0123] The polyanion material prepared above is used as the active material of the battery positive electrode material for the preparation of sodium ion batteries. The specific steps are: b Mn x T i y Mo a M z (PO4)3 powder was mixed with acetylene black and binder polyvinylidene fluoride (PVDF) in a mass ratio of 80:10:10, and an appropriate amount of N-methylpyrrolidone (NMP) solution was added. The mixture was ground in a dry environment at room temperature to form a slurry. The slurry was then evenly coated on the current collector aluminum foil and dried under an infrared lamp before being cut into (10×10) mm 2 The electrode was dried at 110°C for 10 hours under vacuum conditions and then transferred to a glove box for use.
[0124] The assembly of the simulated battery was carried out in a glove box with an Ar atmosphere. Metallic sodium was used as the counter electrode and NaClO4 / diethyl carbonate (EC:DEC) solution was used as the electrolyte to assemble a CR2032 button cell. The charge and discharge test was carried out using the constant current charge and discharge mode. The rate and cycle performance were tested under the conditions of a discharge cut-off voltage of 2.5V and a charge cut-off voltage of 4.3V.
[0125] The input amount of different carbon sources also has a certain impact on the system. The first week charge and discharge curves of comparative examples 1-3 at 0.1C rate are as follows: Figure 5When the carbon source input amount is 1.0 mol, the first week discharge capacity of Na3TiMn(PO4)3 is 97 mAh / g. The first week charge and discharge curve comparison of Comparative Example 1 and Examples 1, 4, 5, 9, 10 at 0.1C rate is shown in the figure below. Figure 6 It can be found that Mo doping and co-doping with other elements can improve the discharge capacity of Na3TiMn(PO4)3. By adjusting the ratio of co-doping elements, the first cycle charge-discharge curves of Examples 19 to 21 at 0.1C rate are as follows: Figure 7 , different addition amounts of M are still effective for the material. When the addition amount of Zn is 0.1, 0.2, and 0.3, the discharge capacity is 109 mAh / g, 109 mAh / g, and 114 mAh / g, respectively. Comparison of the cycle and rate performance of Example 4 and Comparative Example 1 (such as Figure 8 , 9 ) It can be found that the co-doping of Mo and Li significantly improves the cycle stability and rate performance of the material, which reflects the excellence of the material obtained by the present invention.
[0126] It can be seen from the comparison of the above examples that compared with the undoped Na3TiMn(PO4)3 positive electrode material, the material of the present invention has excellent electrochemical performance. In addition to the excellent rate and cycle performance of phosphate polyanion materials, Mo fully activates Mn 2+ / Mn 4+ The electrochemical activity of the battery has significantly improved its capacity.
[0127] The preparation method of a Mo-doped polyanion material containing Ti and Mn provided in an embodiment of the present invention is simple to prepare, and the elements sodium, titanium, manganese and a trace amount of Mo contained are all non-toxic and safe elements with high abundance in the earth's crust, so the manufacturing cost is low. The sodium ion secondary battery containing the Mo-doped polyanion material containing Ti and Mn of the present invention is simple to prepare, and it is found in a half-cell test that the material not only has ultra-high mass specific capacity and specific energy, but also has a very beneficial cycle life, has great practical value, and can be used for large-scale energy storage equipment of solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
[0128] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A Mo-doped polyanion positive electrode material, characterized in that: The Mo-doped polyanion positive electrode material has a chemical formula of Na b Mn x Ti y Mo a M z (PO4)3 is composed of Mo-doped materials and amorphous carbon-coated materials; wherein a=0.01-0.2, b=2.5-4.0, x=0.8-1.5, y=0.5-1.2, z=0-0.5; M is an element co-doped with Mo, including: Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , Al 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc 3+ One or more of; the valence state of the element Mo is +6, where Mo 6+ The doping of Na + The migration barrier of the Mo-doped polyanion cathode material is Na + The Mn element migrates through three pathways, including: from the Na1 position to the Na2 position in the NASICON structure, through the gap between the PO4 tetrahedron and the MO6 octahedron, and across the channel between adjacent MO6 octahedrons, thereby causing the valence state of the Mn element used for charge compensation in the process of sodium insertion and extraction in the positive electrode material to be in the Mn 2+ -Mn 3+ -Mn 4+ Transition between.
2. The Mo-doped polyanion positive electrode material according to claim 1, characterized in that: The Mo-doped polyanion positive electrode material is used as a positive electrode active material for a sodium ion secondary battery.
3. A method for preparing the Mo-doped polyanion positive electrode material according to claim 1, characterized in that: The preparation method is a solid phase method, comprising: The required stoichiometric amounts of 100 wt% to 120 wt% of Na source, phosphorus source, Mn source, Ti source, Mo source, M source and carbon source are mixed in proportion to form a precursor; wherein M is an element co-doped with Mo, specifically including Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , Al 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc 3+ One or more of; Ball-milling the precursor to obtain precursor powder; Placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 550° C. to 850° C. for 2 to 24 hours; The heat-treated product is ground to obtain the Mo-doped polyanion positive electrode material.
4. The preparation method according to claim 3, characterized in that: The Na source includes one or more of sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium acetate (CH3COONa), sodium oxalate (Na2C2O4), sodium nitrate, sodium sulfate (Na2SO4), sodium bisulfate (NaHSO4), and sodium citrate (C6H5Na3O7); The phosphorus source includes one or more of: ammonium dihydrogen phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), phosphoric acid (H3PO4), disodium hydrogen phosphate (Na2HPO4), sodium dihydrogen phosphate (NaH2PO4); The Ti source includes: titanium isopropoxide (C 12 H 28 O4Ti), tetrabutyl titanate (C 16 H 36 O4Ti), di(2-hydroxypropionic acid) diammonium dihydroxide titanium (C3H9NO7Ti), titanium dioxide (TiO2), titanyl sulfate (TiOSO4), titanium sulfate (Ti(SO4)2) or one or more thereof; The Mn source includes one or more of manganese acetate (Mn(CH3COO)2), manganese monoxide (MnO), manganese dioxide (MnO2), manganese tetraoxide (Mn3O4), manganese carbonate (MnCO3), manganese sulfate (MnSO4), manganese oxalate (MnC2O4), and manganese nitrate (Mn(NO3)2); The Mo source includes: ammonium molybdate ((NH4)6Mo7O 24 ), phosphomolybdic acid (H3PMo 12 O 40 ), ammonium phosphomolybdate ((NH4)3PMo 12 O 40 ), molybdenum trioxide (MoO3), molybdenum dioxide (MoO2), molybdenum acetate (C8H 12 Mo2O8), molybdenum dioxynitrate (MoO2(NO3)2), molybdenum acetylacetonate (C 10 H 14 MoO6) or more; The carbon source includes: glucose (C6H 12 O6), starch, citric acid (C6H8O7), ascorbic acid (C6H8O6), polyvinyl alcohol, polyethylene oxide, polydopamine, polyacrylonitrile, polyvinyl pyrrolidone, carbon nanotubes, carbon fibers, and graphene; The M source includes: an oxide corresponding to the M element (M x O y )、Acetate(M(CH3COO) z )、nitrate(M(NO3) z ) one or more.
5. A method for preparing the Mo-doped polyanion positive electrode material according to claim 1, characterized in that: The preparation method is a sol-gel method, comprising: The required stoichiometric amounts of 100wt% to 120wt% of Na source, phosphorus source, Ti source, Mn source, Mo source, M source and carbon source are mixed in proportion, dispersed with a solvent and continuously heated and stirred to form a gel, and evaporated to obtain a precursor powder; wherein M is an element co-doped with Mo, specifically Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , Al 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc 3+ One or more of; Placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 550° C. to 850° C. for 2 to 24 hours; The heat-treated product is ground to obtain the Mo-doped polyanion positive electrode material.
6. The preparation method according to claim 5, characterized in that: The Na source includes one or more of sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium acetate (CH3COONa), sodium oxalate (Na2C2O4), sodium nitrate, sodium sulfate (Na2SO4), sodium bisulfate (NaHSO4), and sodium citrate (C6H5Na3O7); The phosphorus source includes one or more of: ammonium dihydrogen phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), phosphoric acid (H3PO4), disodium hydrogen phosphate (Na2HPO4), sodium dihydrogen phosphate (NaH2PO4); The Ti source includes: titanium isopropoxide (C 12 H 28 O4Ti), tetrabutyl titanate (C 16 H 36 O4Ti), di(2-hydroxypropionic acid) diammonium dihydroxide titanium (C3H9NO7Ti), titanium dioxide (TiO2), titanyl sulfate (TiOSO4), titanium sulfate (Ti(SO4)2) or one or more thereof; The Mn source includes one or more of manganese acetate (Mn(CH3COO)2), manganese monoxide (MnO), manganese dioxide (MnO2), manganese tetraoxide (Mn3O4), manganese carbonate (MnCO3), manganese sulfate (MnSO4), manganese oxalate (MnC2O4), and manganese nitrate (Mn(NO3)2); The Mo source includes: ammonium molybdate ((NH4)6Mo7O 24 ), phosphomolybdic acid (H3PMo 12 O 40 ), ammonium phosphomolybdate ((NH4)3PMo 12 O 40 ), molybdenum trioxide (MoO3), molybdenum dioxide (MoO2), molybdenum acetate (C8H 12 Mo2O8), molybdenum dioxynitrate (MoO2(NO3)2), molybdenum acetylacetonate (C 10 H 14 MoO6) or more; The carbon source includes: glucose (C6H 12 O6), starch, citric acid (C6H8O7), ascorbic acid (C6H8O6), polyvinyl alcohol, polyethylene oxide, polydopamine, polyacrylonitrile, polyvinyl pyrrolidone, carbon nanotubes, carbon fibers, and graphene; The M source includes: an oxide corresponding to the M element (M x O y )、Acetate(M(CH3COO) z )、nitrate(M(NO3) z ) one or more; The solvent includes one or more of water, methanol, ethanol and ethylene glycol.
7. A method for preparing the Mo-doped polyanion positive electrode material according to claim 1, characterized in that: The preparation method is a spray drying method, comprising: The required stoichiometric amounts of 100wt% to 120wt% of Na source, phosphorus source, Ti source, Mn source, Mo source, M source and carbon source are mixed in proportion, dispersed with a solvent and continuously heated and stirred to form a slurry; wherein M is an element co-doped with Mo, specifically Fe 3+ , Zn 2+ ,Mg 2+ , Ni 2+ , Li + , Al 3+ , Si 4+ , Zr 4+ ,Cr 3+ , Nb 5+ , Sc 3+ , Nb 5+ , Sc 3+ One or more of; Spray drying the slurry to obtain a precursor powder; Placing the precursor powder in an atmosphere furnace and heat treating it in an Ar gas atmosphere at 550° C. to 850° C. for 2 to 24 hours; The heat-treated product is ground to obtain the Mo-doped polyanion positive electrode material.
8. The preparation method according to claim 7, characterized in that: The Na source includes one or more of sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium acetate (CH3COONa), sodium oxalate (Na2C2O4), sodium nitrate, sodium sulfate (Na2SO4), sodium bisulfate (NaHSO4), and sodium citrate (C6H5Na3O7); The phosphorus source includes one or more of: ammonium dihydrogen phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), phosphoric acid (H3PO4), disodium hydrogen phosphate (Na2HPO4), sodium dihydrogen phosphate (NaH2PO4); The Ti source includes: titanium isopropoxide (C 12 H 28 O4Ti), tetrabutyl titanate (C 16 H 36 O4Ti), di(2-hydroxypropionic acid) diammonium dihydroxide titanium (C3H9NO7Ti), titanium dioxide (TiO2), titanyl sulfate (TiOSO4), titanium sulfate (Ti(SO4)2) or one or more thereof; The Mn source includes one or more of manganese acetate (Mn(CH3COO)2), manganese monoxide (MnO), manganese dioxide (MnO2), manganese tetraoxide (Mn3O4), manganese carbonate (MnCO3), manganese sulfate (MnSO4), manganese oxalate (MnC2O4), and manganese nitrate (Mn(NO3)2); The Mo source includes: ammonium molybdate ((NH4)6Mo7O 24 ), phosphomolybdic acid (H3PMo 12 O 40 ), ammonium phosphomolybdate ((NH4)3PMo 12 O 40 ), molybdenum trioxide (MoO3), molybdenum dioxide (MoO2), molybdenum acetate (C8H 12 Mo2O8), molybdenum dioxynitrate (MoO2(NO3)2), molybdenum acetylacetonate (C 10 H 14 MoO6) or more; The carbon source includes: glucose (C6H 12 O6), starch, citric acid (C6H8O7), ascorbic acid (C6H8O6), polyvinyl alcohol, polyethylene oxide, polydopamine, polyacrylonitrile, polyvinyl pyrrolidone, carbon nanotubes, carbon fibers, and graphene; The M source includes: an oxide corresponding to the M element (M x O y )、Acetate(M(CH3COO) z )、nitrate(M(NO3) z ) one or more; The solvent includes one or more of water, methanol, ethanol and ethylene glycol.
9. A positive electrode sheet for a sodium ion secondary battery, characterized in that: The positive electrode sheet comprises: a current collector, a conductive additive coated on the current collector, a binder and the Mo-doped polyanion positive electrode material as claimed in claim 1.
10. A sodium ion secondary battery comprising the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Vanadium sodium phosphate composite material as well as preparation method and application thereof
CN103000884A
Cathode material, electrode piece, secondary cell and application of aqueous-solution secondary cell
CN104795564A
Cited By
Surface-modified polyanion positive electrode material, preparation method thereof and battery
CN120727774A